Absurdity In Stillness: A Biographical Approach to The Water Station by Ōta Shōgo - Sari, Sari Riska Rosmiati; R. Myrna Nur Sakinah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research explores Ōta Shōgo’s The Water Station using a biographical lens, concentrating on three key aspects of absurdist theater: the Anti-Hero, Anti-Dialogue, and Anti-Climax. Breaking away from conventional storytelling methods, the play introduces a cast of anonymous characters who move gradually and silently across the stage, briefly stopping at a leaking water pipe. These characters represent the Anti-Hero—individuals lacking a distinct purpose, choice, or identity. The performance's lack of spoken words introduce a powerful Anti-Dialogue component, substituting conversation with silence and physical gestures, which symbolically mirrors the playwright’s experiences of trauma and disillusionment following the war. Moreover, the story does not follow a typical climax or conclusion, utilizing Anti-Climax to highlight the meaningless repetition inherent in human life. Through an examination of Ōta’s personal history—especially his experiences of displacement during World War II and his interest in the concepts of time, slowness, and stillness—this paper illustrates how these influences shaped the play's form and tone. The study emphasizes that non-Western absurdist art can arise from deeply personal and historical backgrounds. Ultimately, The Water Station creates a reflective theatrical experience where silence communicates more than spoken words, encouraging viewers to engage with the themes of emptiness, ambiguity, and the quiet beauty of existence.